A Method for the Regularization of One Class of Dual Series Equations - Brovenko, A. V.; Melezhik, P. N.; Poedinchuk, A. К. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We propose a method for the regularization of one class of systems of dual series equations to which numerous problems in theoretical and mathematical physics are reduced.